2014
DOI: 10.3892/etm.2014.1763
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of multi-slice spiral computed tomography angiography and three-dimensional reconstruction in the diagnosis of double aortic arch

Abstract: The aim of this study was to evaluate the clincal value of multi-slice spiral computed tomography (MSCT) in the diagnosis of double aortic arch (DAA) and analyze the associated angiography and 3D reconstruction imaging to increase the accuracy of DAA diagnosis. Clinical and imaging data from 15 patients diagnosed with DAA by MSCT were summarized and compared with the corresponding surgical observations. The DAA diagnosis by MSCT for the 15 patients was confirmed by the surgical observations. A total of 13 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…It illustrates the arch dominance and tracheal compression. We used it in 59 cases, and our results match the results of many reportsin which all cases were diagnosed by contrastenhanced MSCT [10,11]. On contrary, in Raghavan`s study, they used Magnetic resonant Imaging (MRI), but as we notice, this was a relatively old study [3].…”
Section: Discussionsupporting
confidence: 66%
“…It illustrates the arch dominance and tracheal compression. We used it in 59 cases, and our results match the results of many reportsin which all cases were diagnosed by contrastenhanced MSCT [10,11]. On contrary, in Raghavan`s study, they used Magnetic resonant Imaging (MRI), but as we notice, this was a relatively old study [3].…”
Section: Discussionsupporting
confidence: 66%
“…In our study echocardiography succeeded in diagnosis of nine cases with DAA and failed in five, four cases were diagnosed by echocardiography as right aortic arch while three of them diagnosed by MDCT as DAA with dominant right arch and one case showed DAA with atretic left arch, also one case was diagnosed by echocardiography as left aortic arch, but it was diagnosed by MDCT as DAA with dominant left arch. Chen et al 23 reported that DAA diagnosed by MDCT for fifteen cases and all cases confirmed by surgical observation and total of thirteen cases were diagnosed double open arches, nine of them showed dominant right arch, two showed dominant left arch and two seen with balanced right and left arches. Two cases were show one atretic arch and the other arch was open, in both cases the atretic arch was the left.…”
Section: Discussionmentioning
confidence: 97%
“…8 At the same time, CTA is the principal diagnostic technique that enables rapid and high spatial-resolution evaluation of vascular anomalies noninvasively, in addition to assessment of tracheal or esophageal compression. 9 Magnetic resonance imaging can be an alternative non-invasive technique to prevent radiation exposure and the need of iodinated contrast material, although it usually produces worse image reconstruction, density, and time resolutions than those of CTA. 10 We routinely perform truncal 3D-CTA prior to CAS to assess the risk of cholesterol embolism syndrome as well as the anatomical suitability for CAS.…”
Section: Discussionmentioning
confidence: 99%